Three Essays on the Behavioral Ecology of Markets and Capitalism - Garrison, Jeremy T., author; Fremstad, Anders, advisor; Braunstein, Elissa, committee member; Kroll, Stephan, committee member; Zahran, Sammy, committee member (Colorado State University. Libraries, 2026)
In this dissertation, I employ theoretical evolutionary models and empirical evidence from folklore, ethnography, and economic experiments to explore the evolutionary and contextual effects of markets and capitalism on behavior.In the first chapter, I use evolutionary game theory to examine how empathy evolves in various social-economic ecologies. I situate the evolutionary game on a network with distinct social and economic layers (where strategy transmission and game interactions occur, respectively), and I define empathy as cooperating conditional on social proximity. The results reveal that when interactions occur among both familiars and strangers, discriminatory empathy outperforms unconditional cooperation, but when interactions occur only among strangers, empathy produces no cooperation. The results illustrate that if behaviors spread among familiars, familiarity serves as a proxy for behavioral relatedness; in this way, conditioning cooperation on familiarity concentrates the benefits of cooperation among cooperators, allowing this behavior to persist and spread. In the second chapter, I employ global folklore and ethnographic text as data to analyze the social and cultural effects of markets and capitalism. I construct indices for social, cultural, and economic characteristics based on the textual prevalence of relevant words and apply regression analysis to these indices. The results suggest that markets and capitalism are associated with decreased ecocentrism and increased stratification and that, in folklore, markets are associated with increased moral content. While markets are weakly associated with increased prosociality, capitalism is associated with decreased prosociality. I also estimate the markets coefficients using distance from historic trade route as an instrument, providing some support for a causal interpretation. In the third chapter, I seek to clarify the ambiguities and resolve the apparent contradictions on the relationship between markets and prosociality by assembling a theoretical framework and conducting a meta-analysis of the experimental evidence. Using a theoretical synthesis of evolutionary theory, game theory, and political economy, I argue that markets represent social, psychological, and economic situations that influence both the evolution and the behavioral expression of social preferences. I apply the technique of meta-regression to the findings of 242 experiments to analyze the within-study effects of anonymity, ephemerality, market framing, and country-level market exposure on prosociality. The meta-data reveal a negative effect of market-related contexts on prosociality but no effect of market exposure. Taken together, these essays analyze empirically and theoretically the behavioral ecology of markets and capitalism.